Development of a Core Outcome Set for clinical trials aimed at improving antimicrobial stewardship in care homes. (26th March 2021) - Nguyen, H Q; Bradley, D T; Tunney, M M; Hughes, C M
Abstract: Introduction: Diverse outcomes reported in clinical trials to improve antimicrobial stewardship (AMS) in care homes has hindered evidence synthesis [1]. We previously reported that a number of outcomes for care home AMS which may be important to healthcare professionals and relatives of care home residents had not been measured in previous trials [2]. It is essential to generate a set of important outcomes (a core outcome set – COS) for future studies of AMS interventions in care homes. Aim: To develop a COS for use in clinical trials aimed at improving AMS in care homes. Methods: A refined inventory of outcomes for AMS interventions in care homes, compiled from a previous study [2], was presented in a three-round international Delphi consensus survey, followed by an online consensus exercise. Stakeholders engaged in AMS in care homes (e.g. healthcare professionals, representatives of care home residents) were invited to participate, having been identified through the research team's contacts and knowledge of relevant organisations. A 9-point Likert scale was used during the consensus procedures and an outcome was included in the COS if 80% or more of participants scored between 7 and 9, and 15% or less scored between 1 and 3. Less stringent criteria for inclusion were also applied if the final COS comprised fewer than three outcomes. Subsequently, a suitable outcome measurement instrument (OMI) was selected for each outcome in the COS using the following steps: finding existing OMIs in the literature and consulting with experts, assessing the quality of OMIs, and selecting one OMI for each core outcome via a two-round international Delphi consensus exercise. Consent was obtained from all participants taking part in all consensus procedures. Results: The initial inventory of 14 outcomes was presented to 82 international Delphi panellists from 17 countries in the first round who also suggested three additional outcomes. These 17 outcomes were rated again in two further rounds, with consensus achieved for ten outcomes. A subsequent online consensus exercise with twelve participants from Northern Ireland, including the research team, reached consensus to include five outcomes in the COS (Table 1). Regarding selection of OMIs for the COS, 17 OMIs were identified through literature searches and experts' suggestions. Based on quality assessment, three OMIs - 'Number of antimicrobial courses started per 1000 resident-days', 'Rate of antimicrobial days of therapy per 1000 resident-days', and 'Van Buul algorithms to evaluate appropriateness of initiating or withholding antibiotics' - were selected for a two-round Delphi exercise with 59 participants from 16 countries. Consensus was reached to select two OMIs for the COS, as presented in Table 1. Conclusion: This is the first study to develop a COS for use in clinical trials aimed at improving AMS in care homes. Although we recruited few representatives from advocacy groups for older people, care home staff and managers, there was common agreement for inclusion of a number of outcomes. This COS represents the minimum that should be used in research and trialists may consider exploring other outcomes as reported in previous studies. References: 1. Nguyen HQ, Tunney MM, Hughes CM. Interventions to Improve Antimicrobial Stewardship for Older People in Care Homes: A Systematic Review. Drugs and Aging. 2019;36(4):355–69. 2. Nguyen HQ, Bradley DT, Tunney MM, Hughes CM. Antimicrobial Stewardship in Care Homes: Outcomes of Importance to Stakeholders. J Hosp Infect. 2020 Jan 27;104(4):582–91.